From Near and Far: On the Role of Distance in Changing Professional Services - Adams, Tracey L.; Brock, David M.; Muzio, Daniel; Amis, John (The Journal of applied behavioral science, 2025)
In this editorial, we consider how technology, globalization, and organizational changes have led to professional services being delivered increasingly at a distance. We argue that the impacts of these changes are felt at individual, organizational, and institutional field levels. Impacts include changes in professional career trajectories, collegiality and collaboration, and altered client–professional relations. These developments generate new challenges for governance and organizing across borders. While existing research is often optimistic about what these changes mean for professionals and consumers, some scholars raise concerns about their impact on professional–client interactions, trust, and service quality. In addition to examining these areas, we suggest opportunities for future research that can further our understanding of the implications of these changes for the provision and organization of professional services.